THE ROLE OF SERVICE QUALITY AND TRUST ON CONSUMER LOYALTY AT PT. HENSON ALFA GROS PEKANBARU - Agus Hocky; Lidyana Lidyana; Astri Ayu Purwati (Institut Bisnis dan Teknologi Pelita Indonesia, 2020)
Consumer loyalty is very important for a company, because the rewards of loyalty are long-term and cumulative, which means that the longer the consumer loyalty the greater the profit that can be obtained by the company from a consumer. The purpose of this study was to determine the effect of Service Quality and Trust on Consumer Loyalty at PT. Henson Alfa Gros Pekanbaru. The population in this study were all consumers of PT. Henson Alfa Gros is on Pekanbaru and has made transactions more than 2 times. The number of respondents in this study was 100 businesses. The data collection technique that was used is the questionnaire method. Questionnaire is a way of collecting data through a list of questions that the author has prepared aimed at respondents who will be sampled, while for data analysis techniques using multiple linear regression analysis, F-test, t-test and coefficient of determination. The results of the study show that Trust has an effect on Consumer Loyalty and Service Quality has no effect on Consumer Loyalty at PT. Henson Alfa Gros Pekanbaru.